Recurrent Hodgkin lymphoma: toward a new definition of candidates for autologous stem cell transplant in the era of positron emission tomography scan and novel agents. Issue 7 (July 2015) - Pinto, Antonello; Corradini, Paolo; Mussetti, Alberto; Zinzani, Pier Luigi
Abstract Standard treatment for patients with Hodgkin lymphoma (HL) unresponsive to upfront therapy or relapsing after primary treatment (RR-HL) consists of salvage chemotherapy followed by autologous stem cell transplant (ASCT). ASCT outcomes are essentially related to two factors: disease burden at the time of transplant and comorbidity status of the patient. Positron emission tomography (PET) scan is a very sensitive diagnostic instrument to measure disease status. In fact, a negative PET status before ASCT is a well-known positive prognostic factor in patients with RR-HL. The recent introduction of the biologically targeted agent brentuximab vedotin has allowed us to treat RR-HL more efficaciously with less toxicity for the patient. Use of this new agent could help achieve a PET-negative status before ASCT in a larger percentage of patients, without severe toxicities, thereby improving ASCT outcomes. Herein we discuss the current evolving scenario of RR-HL treatment.